Effect of rice husk surface modification by LENR on the mechanical properties of NR/HDPE reinforced rice husk composite - Rahmadini Syafri,; Ishak Ahmad,; Ibrahim Abdullah, (Universiti Kebangsaan Malaysia, 2011)
Surface modification of rice husk (RH) with alkali pre-treatment (NaOH solution 5% w/v) was carried out at the initial state to investigate the effect of surface treatment of fibre on the surface interaction between fibre and rubber. Further modification of RH surfaces after alkali treatment was using Liquid Epoxidized Natural Rubber (LENR) coating at three concentrations, 5%, 10%, and 20% wt LENR solution in toluene. Interfacial morphology and chemical reactions between RH fibre and rubber were analyzed by FTIR and Scanning Electron Microscope (SEM). It was found that 10% wt LENR solution gave the optimum interaction between fibre and rubber. Matrix and composite blends derived from 60% natural rubber (NR), 40% high density polyethylene (HDPE) reinforced with RH fibre were prepared using an internal mixer (Brabender Plasticoder). Result showed that pre-treatment of RH treated with 5% NaOH followed by treatment with 10% LENR solution given the maximum interaction between fibre and matrix that gave rise to better mechanical properties of the composites.